Survival strategies and the robustness and resilience of exporters amidst wild card COVID-19 shocks - Adrian Mendoza (University of the Philippines, School of Economics (UPSE), 2025)
Using a large firm-level dataset assembled from the World Bank Enterprise Surveys and COVID-19 Follow-up Surveys for 23 countries, this study examined the survival, robustness, and resilience of exporters amidst the economic hibernation induced by COVID-19 lockdowns. While the stylized facts suggest that "positive" ("negative") technology-intensive emergency innovations were positively (negatively) related with exporting, the Weibull and negative binomial regressions show that most of these strategic responses were either insignificant or negatively related with the ability of exporters to weather and recover from COVID-19 disruptions. With a limited window for learning, this implies that the documented emergency innovations were likely signs of distress and mainly used by exporters as last-ditch efforts to avoid exit. Another explanation is that the pandemic shocks crowded out the supposed positive effects of these emergency responses, with stringency and idiosyncratic negative supply and demand shocks significantly accelerating the failure time of exporters; while the duration of disruptions (proxied by vaccine delay) partly prolonged the expected speed of recovery. In the face of wild card COVID-19 shocks, superior pre-pandemic capabilities, especially labor productivity, mattered more for the survival, endurance, and recovery of exporters. Importing also allowed exporters to ease local supply chain constraints, indicating that firms with stronger international linkages had lower exit probabilities despite their greater exposure to global shocks. The preceding results favor the self-selection argument, while positive learning effects may have been muted by fast evolving pandemic shocks. This highlights the importance of early investment in capabilities to future-proof firms against wild card crises.
Keywords: D22; D24; F10; L21; L25; O33; 330; COVID-19; exporters; survival; robustness; resilience; wild card